The allometric relationships between biomass and nitrogen of vegetative organs affect crop N status in maize at silking stage - Maltese, Nicolás; Maddonni, Gustavo Angel; Melchiori, Ricardo Jose; Ciampitti, Ignacio A.; Caviglia, Octavio (Elsevier, 2023)
In maize (Zea mays, L.) changes in the partitioning of biomass (W) and nitrogen (N) between organs linked to photosynthetically active tissues, such as leaves (with high N concentration, %N) and organs related to supporting functions, such as stems (with low %N) at silking stage, could modify the diagnosis of crop N status (i.e., N nutrition index, NNI) for fertilizer N recommendations. To test this hypothesis we used a database of maize measurements performed at silking stage of crops cultivated under different N fertilization rates, plant densities, hybrids, and sowing dates, to investigate i) the allometric relationships between %N and W of leaves (%NL and WL) and stems (%NS and WS), ii) changes in N uptake in vegetative organs for crops with low (<6700 kg ha−1) and high (>6700 kg ha−1) crop W and contrasting NNIs, iii) the responses of crop W at silking stage to N fertilization relative to responses of WL, WS, %NL and %NS, and iv) the inclusion of the %NL/%NS ratio in a predictive model of relative grain yield based on crop NNI at silking. Variations of WS (from 2143 to 10,067 kg ha−1) were greater than those of WL (from 1010 to 4107 kg ha−1), whereas the values of WL/WS ratio (for low W crops) and leaf/stem ratio for N uptake (for both high and low W crops) were lower for NNI> 1.1 than for NNI< 0.9, reflecting the key role of stems as N storage organs when N is non-limiting. Changes in WS largely modulate the response of crop W to N fertilization, while changes in %NL largely modulated the response of crop %N to N fertilization for high W crops. Optimal crop N status (i.e., NNI=∼1) was attained with a greater %NL/%NS ratio for high (2.0) than for low (1.2) W crops, suggesting that this allometric ratio should be taken into account at this crop growth stage, particularly for low crop W. Accordingly, the prediction of relative grain yield based on NNI at silking was improved by the inclusion of %NL/%NS. Therefore, our results are useful to better understand the response of maize crop W, grain yield, and crop %N (for leaves and stems) to late N fertilization, adding valuable insights to improve current NNI-based N diagnostic tools.